Remaining Service Life Struktur Conveyor D pada Tambang Batubara PT XYZ di Kabupaten Kotabaru, Provinsi Kalimantan Selatan - Dwiki Zulkifly Ardiansa; Elfida Moralista; Iswandaru (UNISBA Press, 2022)
Abstract. Activity moving products requires the help of mechanical devices that are able to deliver materials efficiently and condicively, beside there are mechanical devices called Conveyor. Conveyors made from a carbon steel with the prone condition oxidation due to direct contact with the surrounding environment. As a result, the metal composition based conveyor structure will be experience a process a loss material composition called Corrosion. The methodoly research in that case using the method reduction thickness of the conveyor structure with the divice Ultrasonic Thickness Gauge TT 130. Environmental conditions in the conveyor structure are have an average highest rainfall in 2020 is 292,08mm/year, average relative highest humidity in 2021 is 86,75%, and average highest air temperature in 2020 is 27.53°C, the research was conducted on 90m long Conveyor structure which have divided into a 3 segments with 25 test points. The goal of research was find out the type of Corrosion, Corrosion Control, Remaining Service Life structure and the Corrosion rate of the conveyor stucture. Abstrak. Kegiatan pemindahan material–material hasil tambang memerlukan bantuan alat mekanis yang mampu mengantarkan material secara efisien dan kondusif, diantara alat mekanis tersebut adalah Conveyor. Conveyor berbahan baja karbon yang rawan mengalami oksidasi akibat bersentuhan langsung dengan lingkungan sekitar. Akibatnya Struktur Conveyor yang berbahan dasar logam akan mengalami proses kerusakan yang dinamakan korosi. Metedologi penelitian yang gunakan ialah metoda pengurangan ketebalan struktur Conveyor dengan menggunakan alat Ultrasonic Thickness Gauge TT 130. Kondisi lingkungan daerah Struktur Conveyor memiliki jumlah curah hujan rata–rata tertinggi tahun 2020 sebesar 292,08 mm/ tahun, kelembapan relatif rata–rata tertinggi tahun 2021 sebesar 86,75%, dan temperatur udara rata–rata tertinggi tahun 2020 sebesar 27,53°C. Penelitian dilakukan terhadap Struktur Conveyor D sepanjang 90m yang terbagi atas 3 segmen dengan 25 Test point. Penelitian bertujuan untuk mencari tahu jenis korosi, pengendalian korosi, Sisa Umur pakai Struktur Conveyor dan laju korosi.